OPEN SOURCE AS A DRIVER FOR FRUGAL INNOVATION - Alamsyah, Purnama; Oktaviyanti, Dini (Pusat Penelitian Perkembangan Iptek, LIPI, 2012)
The changing times require people to be creative and innovative. People are required not only as users but also as a creator of goods thing. People needs to think creative to produce something that useful and also effective and efficient. One thing that in line with the demands of effective and efficient is an open source. Open source stimulates innovation and ensures that ideas can spread rapidly to the creation of a new product. Open source also can drive innovation to ensure sustainable value for companies with different business models. Open source is one of the most inexpensive solution and the most effective in the transfer of technology and knowledge in particular for developing countries. Open source does not just offer a low cost alternative to acquire the technology but also network-based cooperation. Characteristics of the open source compatible with the concept of frugal innovation. Concept of frugal innovation itself responding to resource constraints, both financial, material or institutional and using a variety of methods that transform obstacles into advantages. Frugal innovation minimizing the use of resources in the development, production and delivery, or by utilizing new ways that can dramatically produce products and services become less expensive. The success of frugal innovation is not only determined by its low cost but also provide an alternative edge that also can be made on a large scale. In addition, although not always, explicitly frugal innovation has a social mission. Through this paper the author aims to explore open source as a driver of frugal innovation. Spirit of open source along with the concept of frugal innovation. This paper attempts to explore the role of open source as a driver of frugal innovation and to explain that the spirit of open source along with the concept of frugal innovation.